The Concept of the African Family as a Symbol for Ecumenical Dialogue and an Inclusive Theology: Perspectives from an African Woman Theologian - Barutwanayo, Felix (Lumen et Vita, 2024)
Diversity is an outstanding characteristic of the world today, experienced at all levels of human relationships. Differences between people may lead to tensions and complexities in communication, even when the parties are self-aware and acknowledge each other’s identity. Interreligious encounters are particularly complex, due to the importance to a religious adherent of the worldview that they affirm. What models or symbols of mediation can best promote respectful and mutually enriching relationships across differences in religious identity? In this context of worldwide diversity, Mercy Amba Oduyoye proposes the symbol of the African family as a model for ecumenism and interreligious dialogue. I examine the symbolic significance of the concept of the family in Africa, and the unique characteristics it can offer to the global challenge of interreligious dialogue, particularly dialogue that includes non-Abrahamic religious or philosophies. I conclude that while the ontological and functional meaning of the African family makes it an attractive symbol for ecumenical dialogue, it remains inadequate to support the full inclusion of non-Abrahamic religions and philosophies as well as other marginalized groups.